Protective effects of Sonchus asper (L.) Hill, (Asteraceae) against CCl4-induced oxidative stress in the thyroid tissue of rats - Khan Rahmat (BMC Complementary and Alternative Medicine, 2012)
Abstract Background Sonchus asper (L.) Hill, (Asteraceae) is used in Pakistan as a traditional (“folk”) medicine for the treatment of hormonal disorders and oxidative stress. The present study was aimed to evaluate the efficacy of Sonchus asper (L.) Hill, (Asteraceae) methanolic extract (SAME) on hormonal dysfunction in thyroid tissue after carbon tetrachloride (CCl4)-induced oxidative stress. Methods To examine the effects of SAME against the oxidative stress of CCl4 in thyroid tissue, 30 male albino rats were used. Protective effects of SAME were observed on thyroid hormonal levels, activities of antioxidant enzymes, lipid peroxidation (TBARS) and DNA damage. Results Treatment with CCl4 significantly (P<0.01) reduced the levels of T3 and T4 and increased TSH levels. CCl4 exposure in rats reduced the activities of antioxidant enzymes but increased lipid peroxidation and DNA damage. Co-administration of SAME significantly (P<0.01) improved these alterations with respect to hormonal levels, activities of antioxidant enzymes and lipid peroxidation close to those seen in control rats. Conclusion These results suggest that SAME can protect thyroid tissue against oxidative damage, possibly through the antioxidant effects of its bioactive compounds.